The Effectiveness Of Administration Of Kelor Tea To Increase Hemoglobin Levels In Pregnant Women With Anemia In The Work Area Of Pondok Ranji Tangerang Selatan Puskesmas Working Area - Rukmaini; Ditha Fauziah; Jenny Anna Siauta (Institute of Computer Science (IOCS), 2022)
The prevalence of anemia in pregnant women is increasing every year, including in developing countries such as Indonesia. The higher the prevalence, the more complications that will be encountered such as postpartum bleeding, prolonged labor and other labor complications. Moringa leaves have a high iron content which can increase hemoglobin levels so as to prevent anemia in pregnant women. The purpose of this study was to determine the effectiveness of giving Moringa leaf tea to increase hemoglobin levels in pregnant women with anemia. This research is a quasi-experiment with pre-post test with control group design. The study was conducted in the working area of Pondok Ranji Public Health Center, South Tangerang in 2022. The sample size in the study was 40 respondents consisting of 20 intervention groups and 20 control groups taken by purposive sampling. The research instrument used an observation sheet. The analysis used is the Independent T-Test test which was previously tested for normality and homogeneity. The results of the study on hemoglobin levels before being given Moringa leaf tea an average of 9.69 and after being given Moringa leaf tea an average of 11.12 with an average difference of 1.43, in the control group examination I an average of 9.94 and examination II an average of 10.55 with an average difference of 0.61. There was a significant difference in the mean hemoglobin level between the intervention group and the control group with a significance level of 0.028 < 0.05